Anti-bullying intervention in school context: Feasibility study (Research, Society and Development, 2021)
The aime of this study was to evaluate the feasibility of an anti-bullying intervention in the school context, from quantitative and qualitative criteria. The group intervention, carried out in eight weekly meetings, was applied to nine Elementary School adolescents from a public school in Brazil. The instruments used were: Intervention Evaluation Measure, Observer Evaluation Form and Field Diary. The quantitative aspects observed were: participants’ adherence in the intervention; moderator’s social skills and integrity/fidelity; satisfaction, clarity/understanding and application of contents in daily life. Thematic Content Analysis identified three themes: Application of learning, Engagement and protagonism and Evaluation of the intervention. The results demonstrated a positive evaluation of the intervention and the moderator, with participants' engagement in the proposed activities. Based on the analysis, changes were proposed in some activities of the intervention and in an item of the Evaluation Form. It can be concluded that the intervention proposal has potential and is viable for future studies.